Measuring the Degree of Internationalization (DOI) of Indian Manufacturing Companies - Ramamurthi, Ramakrishnan; Saxena, Rajan; Krishnamoorthy, Bala; Saini, Gordhan (Indian Journal of Marketing, 2021)
Many Indian companies from manufacturing sectors such as industrial, consumer discretionary, and materials have forayed into international markets through exports, overseas ventures, mergers and acquisitions (M&As), joint ventures, etc. Still, there remain unanswered findings to be gained from new research to measure the degree of internationalization (DOI) of international business operations by applying an index, for the first time, to Indian manufacturing companies. Moreover, existing studies, predominantly emanating from developed economies, have explored DOI in the context of developed economies. The extant approaches are limited because explaining the phenomenon of measuring the DOI of firms from emerging economies using frameworks designed for companies in developed countries may lead to incorrect results, as they are characterized by institutional voids like poor governance, greater governmental control, and nascent institutions. This original empirical investigation researched vital phenomena pertaining to Indian manufacturing companies by addressing the gaps outlined above. Researchers can cite germane measures of DOI via the proposed index to support academics and practitioners to determine whether a specific Indian manufacturing company has recently ventured into or plans to launch into the international markets by employing a more thorough composite measure of DOI.